The Influence of Service Quality Toward Customer Satisfaction at CV. Indako Trading Co, Medan - Ika Puspa Satrianny; Benny Lim; Duffin; Eddy Gunawan (Universitas Muhammadiyah Palu, 2023)
The increasing demand of servicing make CV. Indako Trading Co have problem in serve the servicing. The supply of seats isn’t enough for the customers who comes to get servicing. The service advisor is less knowledge, because when customer asked for advice about their motor problem, the service advisor only can reply “let’s the mechanic check the problem”. The next problem is their customer service, their customer service less responsive. The writer chooses the title : The Influence of Service Quality toward Customer Satisfaction at CV. Indako Trading Co, Medan. The writer will use the Parasuraman five service dimensions which are tangible, reliability, responsiveness, assurance, and empathy and Surachandar customer satisfaction dimensions which are core service, human element of service delivery, systematyzation of service delivery, tangibles of service, and social responsibility.The total population in CV. Indako Trading Co is 300 customers. The writer uses the Slovin sampling techniques with 5 % of error tolerate. The sample size is 171 customers. In analyzing data, the writer used some methods such as such as data descriptive, the validity test, the reliability test, the correlation test, the determination test, the linier regression, and the hypothesis test.From the result of coefficient correlation between variable x and variable y, resulted 0.75 which means the service quality has a strong relation (influence) toward the customer satisfaction at CV. Indako Trading Co, Medan. The percentage of service quality toward customer satisfaction is 56.25% and the remaining percentage of 43.75% were affected by other factor of product quality which was not discussed in this skripsi. From the calculation of hypothesis test, The zcount > z table, this means the Null hypothesis (Ho) is rejected and the alternative (Ha) is accepted. The Service quality influences customer satisfaction at CV. Indako Trading Co, Medan.